NYPD red 2 - Patterson, James, 1947-; Karp, Marshall (New York : Grand Central Publishing, 2014)
After being called to a horrible crime scene in Central Park involving a brutally murdered woman on a carousel, Zach and Kylie, detectives with the elite NYPD Red, must uncover the killer while public pressure builds.
Keywords: Detectives -- New York (State) -- New York -- Fiction; Murder -- Investigation -- New York (State) -- New York -- Fiction; Motion pictures -- Production and direction -- New York (State) -- New York -- Fiction; Mystery fiction; Suspense fiction